2016
DOI: 10.1088/1748-9326/11/4/044015
|View full text |Cite
|
Sign up to set email alerts
|

Energy budget increases reduce mean streamflow more than snow–rain transitions: using integrated modeling to isolate climate change impacts on Rocky Mountain hydrology

Abstract: Energy budget increases reduce mean streamflow more than snow-rain transitions: using integrated modeling to isolate climate change impacts on Rocky Mountain hydrology AbstractIn snow-dominated mountain regions, a warming climate is expected to alter two drivers of hydrology: (1) decrease the fraction of precipitation falling as snow; and (2) increase surface energy available to drive evapotranspiration. This study uses a novel integrated modeling approach to explicitly separate energy budget increases via wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 48 publications
(49 reference statements)
4
58
0
Order By: Relevance
“…The greater contribution of warm-season temperature versus cool-season temperature to variability of UCRB flow suggests that evaporation or snowmelt, rather than changes from snow to rain during the cool season, have driven recent reductions in UCRB flow. These results are consistent with the findings of Foster et al (2016), who examined the effects of warming on the hydrology of two mountain watersheds in the central Rocky Mountains and reported that warminginduced shifts in precipitation from snow to rain had a smaller effect on decreases in runoff than did warming-driven increases in summer evapotranspiration.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The greater contribution of warm-season temperature versus cool-season temperature to variability of UCRB flow suggests that evaporation or snowmelt, rather than changes from snow to rain during the cool season, have driven recent reductions in UCRB flow. These results are consistent with the findings of Foster et al (2016), who examined the effects of warming on the hydrology of two mountain watersheds in the central Rocky Mountains and reported that warminginduced shifts in precipitation from snow to rain had a smaller effect on decreases in runoff than did warming-driven increases in summer evapotranspiration.…”
Section: Resultssupporting
confidence: 91%
“…Bureau of Reclamation 2012;Udall and Overpeck 2017). A number of studies have examined the effects of projected future warming on streamflow in the Colorado River basin (Christensen et al 2004;Christensen and Lettenmaier 2007;Hoerling and Eischeid 2007;McCabe and Wolock 2007;Vano et al 2014;Ficklin et al 2013;Kopytkovskiy et al 2015;Foster et al 2016;Udall and Overpeck 2017). All of these studies have indicated that the adverse effects of future warming on Colorado River streamflows are likely to be considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Although we find that slow‐draining catchments have lower elasticity on average and therefore appear less sensitive, these same catchments have more subsurface water storage in late summer available for extraction and therefore may be more vulnerable to increased evaporative demand (Jepsen et al, ; Tague, ). Future work should aim to isolate the mechanisms that control the seasonal partitioning of precipitation into evapotranspiration versus streamflow during periods of increased evaporative demand, for example, using modeling experiments (Foster et al, ) or during extreme events such as the recent California drought (Bales et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar modeling work to this study has been conducted on specific components of hydrologic response to climate change. A recent study on the sensitivity of mountain hydrology to climate-driven changes in the phase of precipitation highlights the importance of energy increases on hydrologic partitioning in snow-dominated watersheds (Foster, Bearup, Molotch, Brooks, & Maxwell, 2016). Furthermore, different warming and drying scenarios result in different recharge patterns for different geologic settings of mountain regions, with greater susceptibility to climate change occurring in areas with greater subsurface water retention (Markovich, Maxwell, & Fogg, 2016).…”
Section: Introductionmentioning
confidence: 99%